Eliminating air pollution disparities requires more than emission reduction - Libby H. Koolik; Robert D. Bullard; Esther Min; Rachel Morello-Frosch; Regan Patterson; Manuel Salgado; Nico Wedekind; Julian D. Marshall; Joshua S. Apte (Proceedings of the National Academy of Sciences, 2025)
In the United States, people of color are disproportionately and unjustly exposed to air pollution. Historically, environmental policy has emphasized aggregate emission reductions, yet major emission reduction scenarios do not sufficiently mitigate relative exposure disparities. Here, we show that without focusing on relative disparity (percent difference) in exposure, the only way to improve air quality and eliminate absolute exposure disparity is to eliminate all emissions (an unlikely outcome). We demonstrate that the relative disparity metric is ethically important and also a controllable societal feature that can reduce absolute disparity in exposure. We illustrate a range of approaches to air pollution policy that go beyond traditional emission reductions to meaningfully address exposure disparities. These strategies should be at the center of the future US environmental policy.